Does entrepreneurial self-efficacy moderate effects of cognitive flexibility and entrepreneurial alertness on entrepreneurial intentions? - Shabeeb Ahmad Gill; Nelly Bencheva; Selcuk Karayel; Muhammad Usman (Entrepreneurial Business and Economics Review (EBER), 2021)
Objective: The objective of this article is to empirically investigate whether entrepreneurial self-efficacy moderates the effects of cognitive flexibility, entrepreneurial alertness on entrepreneurial intentions. It is based on social cognitive theory and person-environment fit theory; the present study aimed to identify the impact of cognitive flexibility, entrepreneurial alertness on entrepreneurial intention. Research Design & Methods: The sample of this study comprised 486 respondents from the public sector business schools of Pakistan. Data were gathered using a self-report administered questionnaire, and hypotheses were tested with structural equation modelling. Findings: The results supported the structured hypotheses of the study where cognitive flexibility positively predicts the conditional direct relationship between entrepreneurial alertness and entrepreneurial intentions. Implications & Recommendations: Our study has some practical implications for the researcher, educationist, and policymakers who are directly and indirectly involved in enhancing the growth of entrepreneurship. Contribution & Value Added: A unique technique adopted to run a second-order moderated mediation model through AMOS v.26 in one-shot. This study contributes to the emerging research of cognitive psychology and entrepreneurship fields and concludes that individuals with a high level of cognitive flexibility, alertness, and self-efficacy are more inclined to pursue a career in entrepreneurship.
Keywords: L26; M13; 330; entrepreneurial self-efficacy; entrepreneurial alertness; entrepreneurial intentions; Second-order moderated mediation; Model 15; User-defined estimand; oneshot robust model; new venture creation